PENGARUH INTENSITAS PENYINARAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JANGGELAN (MESONA PALUSTRIS BL) DI PACITAN - Takim Mulyanto; Agus Suryanto; Zanida Etis Nuriani (Institute of Computer Science (IOCS), 2023)
The aim of the study was to determine the response of different sunlight intensities to the growth and yield of gingergrass plants. The study was conducted in Pakis village at 1,000 meters above sea level, Nawangan district, Bajdan district. The method used was a factorial, fully randomized design. The first factor is to provide four shading levels: 0%, 20%, 40%, 60%, and the second factor is the type of ginger: purple ginger and green ginger. Studies have shown that shade does not significantly affect parameters such as leaf number, plant height, and branch number. Tiller number in shade period showed significant effect. Using wet and dry shrubs can also have a dramatic effect. This shading effect appeared on the plants he four weeks after planting. Observational data show that Zijianglan is highly resistant to sha.